Pembagian Harta Bersama Dalam Perkawinan Menurut Undang-Undang Nomor 1 Tahun 1974 Dan Hukum Islam - Winarno, Winarno (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
Marriage is one of the religious commands that must be done by people who already have the physical and mental abilities to carry it out. In the law state of Indonesia, marriages are regulated by the state regarding the terms and conditions for someone who is going to get married, and both rules are directed at men and women. These rules are contained in Law Number 1 of 1974 and Islamic Law. Therefore, if the marriage does not meet the terms and conditions set, the marriage cannot be carried out. Since marriage is a union between a man and a woman, there will be cooperation, both cooperation in fostering households to achieve harmony and in finding property for survival. Each property obtained by a married couple will become a common property even though in terms of quantity, the one earned by each husband and wife can be different, even the one who earns money is only one of them. However, the marriage between the two makes the property belong together. Although in terms of civil and Islamic law, there are no strict rules regarding shared assets, but because the assets are obtained after marriage, they become shared property. Therefore, if a divorce in the future occurs or one dies, the assets must be divided in half. The rules for the distribution of shared assets do not actually violate the general provisions contained in either positive law or Islamic law.